Effect of foliar application of micronutrients on yield of date palm cv. Halawy (Indian Journal of Arid Horticulture, 2021)
An experiment was carried out to study the effect of foliar application of micronutrients on yield and quality of date palm. The applied treatments were arranged in a randomized block design (RBD) with three replications viz. T, Control, T, ZnSO, (0.5%), T, Borax (0.25 %), T, FeSO, (0.5 %), T. Thiourea (0.l %), T, ZnSO, (0.5 %) + Thiourea (0.1%), T1Borax (0.25%) +Thiourea (0.1%) and T, FeSO, (0.5 %) + Thiourea (0.1%). Application of different micronutrients affects the yield, fruit weight and quality of date palm cv. Halawy. The maximum fruit yield (121.27 kg/palm) and fruit weight (7.8Jg/ berry) were recorded in treatmentT3 (FeSO, 0.5%+ Thiourea 0.1%) while highest TSS (35.42%) was recorded in treatment T, (Borax0.25% + Thiourea 0.1%) followed by treatment T3 (FeSO, 0.5%+Thiourea0.I %).